Gender Differences at the Onset of Autoimmune Thyroid Diseases in Children and Adolescents - Calcaterra, Valeria; Nappi, Rossella E.; Regalbuto, Corrado; De Silvestri, Annalisa; Incardona, Antonino; Amariti, Rossella; Bassanese, Francesco; Clemente, Andrea Martina; Vinci, Federica; Albertini, Riccardo; Larizza, Daniela (Frontiers in Endocrinology, 2020)
Background The incidence of autoimmune thyroid diseases (ATD) may vary with the beginning of reproductive function, although few studies differentiate the incidence before and during the onset of puberty, examining gender bias. We analyzed onset of ATD in a pediatric population to assess gender differences in onset age, disease subtype, pubertal status, autoimmune co-morbidity, family history and treatment, focusing on the interaction between gender and pubertal stage. Patients and methods We retrospectively recorded 382 children and adolescents with ATD. In each patient physical examination was considered. The presence of other associated autoimmune diseases (AD) and familial predisposition were also recorded Results Predominant prevalence was noted in females compared to males (p<0.001), both in Hashimoto’s diseases (HD or HT) and Graves’ disease (GD) (p<0.001). Mean age at diagnosis showed no significant difference between gender (p>0.05). A higher prevalence in pubertal subjects was noted compared to prepubertal (p<0.001, particularly HT in early and GD in late pubertal stage), without gender difference intra-(prepubertal vs pubertal) and inter-puberty groups (prepubertal vs early pubertal vs late pubertal). Both in HT and in GD, the prevalence of autoimmune associated diseases (ADs) was higher in males compared to females (p=0.04), with similar distribution according to the pubertal maturation. The familial predisposition was similarly distributed in both genders (p>0.05) and into pubertal stages (p>0.05). Conclusions Females are more prone to develop ATD during puberty, earlier in HT than in GD. The effect of puberty is not different between genders, supporting the role of additional factors other than hormones. The screening for detection of ATD is recommended in all patients with positive familiarity and other ADs, mostly in males. Considerations of gender in pediatrics are important to define pathogenic mechanisms of ATD and to help in early diagnosis and clinical management.